Perlindungan Hukum Hak Atas Kekayaan IntelektualTerhadap Produk Batik di perusahaan BatikBrotoseno Sragen - Muhammad H, Riza, Inayah, S.H, M.H (2016)
Muhammad Riza H. NIM C 100 080 094. Legal Protection of Intellectual Property Rights in the Company for the Product of Batik Brotoseno Sragen. Faculty of Law. Muhammadiyah University of Surakarta. 2016. The purpose of this study was to analyze the efforts made by the company Batik Brotoseno Sragen to protect its brand and safeguard the law against the designs of batik production company Brotoseno Batik Sragen. This research includes juridical empirical legal research (sociological). Research conducted at the company Batik Brotoseno Sragen. The data source using primary data from interviews. Data were analyzed using qualitative analysis. The results showed that: First, the efforts made by the Company to protect its brand Brotoseno batik product is to apply for registration of the trademark to the Trademark Directorate Director General of Intellectual Property Rights Ministry of Law and Human Rights of the Republic of Indonesia. After a trademark registration application is accepted, then the brand owners obtain legal protection within a period of 10 years; Second, the shape or design motif batik products Brotoseno until now not obtain IPR protection. Because although batik products Brotoseno have fulfilled the elements as objects of industrial design but it would be difficult for batik products Brotoseno to get legal protection, given some of the things that will become an obstacle when requested, namely on: 1) Terms of novelty, the Company's products Batik Brotoseno an improvement or development of designs public that already exist in the community (Article 2 (1) and Article 3 of the Law on Industrial design) 2) has become public domain: batik has been used widely among batik designer (Article 2 ( 1) and (2) of the Law of Industrial Design). Keywords: batik brand protection, batik design product